2005
DOI: 10.1111/j.1744-6570.2005.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Retest Effects in Operational Selection Settings: Development and Test of a Framework

Abstract: This study proposes a framework for examining the effects of retaking tests in operational selection settings. A central feature of this framework is the distinction between within-person and between-person retest effects. This framework is used to develop hypotheses about retest effects for exemplars of 3 types of tests (knowledge tests, cognitive ability tests, and situational judgment tests) and to test these hypotheses in a high stakes selection setting (admission to medical studies in Belgium). Analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
149
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(166 citation statements)
references
References 39 publications
12
149
1
4
Order By: Relevance
“…Again, research is scarce. Lievens et al (2005b) demonstrated that retest effects of SJTs were not larger than those of more traditional tests (cognitive ability). An important moderator seems to be the approach of constructing alternate SJT forms (Clause et al, 1998;Oswald et al, 2005).…”
Section: Fakabilitymentioning
confidence: 99%
“…Again, research is scarce. Lievens et al (2005b) demonstrated that retest effects of SJTs were not larger than those of more traditional tests (cognitive ability). An important moderator seems to be the approach of constructing alternate SJT forms (Clause et al, 1998;Oswald et al, 2005).…”
Section: Fakabilitymentioning
confidence: 99%
“…Kline (2000) recommends that parallel forms reliability should be above r=.70. On balance, the research evidence shows good levels of parallel forms reliability for SJTs, for example: r=.76 (Chan & Schmitt 2002) and r=.66 (Lievens et al 2005b). …”
Section: How Reliable Are Sjts?mentioning
confidence: 99%
“…And improvement will vary with the type of test. Lievens et al (2005) reported retest effect sizes of .30, .40, and .46 for a situational judgment, knowledge, and cognitive ability test, respectively. Hypothesis 3: Tests at lower ranks would correlate with performance on tests at higher ranks.…”
mentioning
confidence: 94%